2015
DOI: 10.1021/acs.jpcc.5b07960
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Au–In Alloy–Oxide Core–Shell Particles as Electrocatalysts for Efficient Hydroquinone Detection

Abstract: The presence of hydroquinone (HQ), a phenol, ubiquitous in nature and widely used in industry needs to be monitored due to its toxicity to the environment. Here we demonstrate efficient detection of HQ using simple, fast and non-invasive electrochemical measurements on ITO electrodes modified with nanoparticles comprising bimetallic Au-In cores and mixed Au-In oxide shells. While bare ITO electrodes show very low activity for the detection of HQ, their modification with Au-In core-shell nanoparticles induces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The electrocatalytic properties of gold nanoparticles (AuNPs) are also well established [24,25,26,27], and a variety of uncapped and capped AuNPs have been successfully used to detect phenols [28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic properties of gold nanoparticles (AuNPs) are also well established [24,25,26,27], and a variety of uncapped and capped AuNPs have been successfully used to detect phenols [28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The responses on MONP-CPEs were consistent with those already reported in bare CPE electrodes (Kilmartin et al, 2001 ), but the presence of MONPs caused shifts in the position of the peaks to lower potentials and/or increases in the intensity of the peaks. This effect could be attributed to the excellent electrocatalytic activity of MONPs due to the mixed valence state found at the nanoparticle surface (Medina-Plaza et al, 2015b ). Depending on the nature of the MONPs used as modifiers, the responses toward a certain compound was more or less enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to perform the statistical analysis, the number of variables was reduced using a data reduction technique based on predefined response “bell-shaped-windowing” curves called “kernels” (Medina-Plaza et al, 2015b ). In this method, each voltammogrammetric curve is multiplied by 10 smooth, bell-shaped windowing functions defined as:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in good correlation with previous studies that have demonstrated that the size of the obtained nanoparticles depends on the concentration of the reducing agent (citrate, nitrite, etc. ), and that this effect can be used to develop colorimetric probes [27,28]. A further observation from analysis of these spectra concerns the broadness of the peaks that are reflecting of a large dispersion of the size of the AuNPs obtained.…”
Section: Resultsmentioning
confidence: 99%